2021
DOI: 10.2478/raon-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of IVF/ICSI cycles in male cancer patients: retrospective analysis of procedures from 2004 to 2018

Abstract: IntroductionFertility preservation is an important aspect of quality of life in oncological patients, and in men is achieved by semen cryopreservation prior to treatment. Results of in vitro fertilization (IVF) procedures in healthy infertile couples are comparable, regardless of whether fresh or cryopreserved semen is used, but are scarce in male oncological patients.Patients and methodsWe performed a retrospective analysis of IVF/intracytoplasmic sperm injection (IVF/ICSI) procedures in infertile couples whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
(48 reference statements)
1
7
1
Order By: Relevance
“…The pregnancy rates and live birth rates were similar in the two groups. 16 In our study, we did not observe any correlation between the frozen sperm concentration and fertility outcomes. These results are important to promote sperm cryopreservation before oncological treatment and should be discussed during fertility preservation counselling.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The pregnancy rates and live birth rates were similar in the two groups. 16 In our study, we did not observe any correlation between the frozen sperm concentration and fertility outcomes. These results are important to promote sperm cryopreservation before oncological treatment and should be discussed during fertility preservation counselling.…”
Section: Discussioncontrasting
confidence: 57%
“…Finally, a 2021 study compared thawed sperm versus fresh sperm used for IVF/ICSI in cancer patients. The pregnancy rates and live birth rates were similar in the two groups 16 . In our study, we did not observe any correlation between the frozen sperm concentration and fertility outcomes.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…It has also been suggested that ICSI may optimize the chances of pregnancy, regardless of the fertility status of the female partner, given the decreased quality of the frozen-thawed test for semen frozen over a long period of time [ 21 , 25 ]. Clinical pregnancy rates for ART cycles ranged from 45.8% to 82% while live birth rates ranged from 35 to 82%, thus demonstrating the achievement of fertility and safe pregnancies with frozen-thawed sperm [ 36 ]. Depalo et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that ICSI may optimize the chances of pregnancy, regardless of the fertility status of the female partner, given the decreased quality of the frozen-thawed test for semen frozen over a long period of time [21,25]. Clinical pregnancy rates for ART cycles ranged from 45.8% to 82% while live birth rates ranged from 35 to 82%, thus demonstrating the achievement of fertility and safe pregnancies with frozen-thawed sperm [36]. Depalo et al [22] concluded that the rates of motility, vitality, and fertilization of thawed semen were significantly lower in patients with testicular tumors and lymphomas than other tumors (35.4% and 50% vs. 71.4%), while there were no differences in the ovum cleavage rate and implantation rates.…”
Section: Discussionmentioning
confidence: 99%